Absence of systemic oxidative stress and increased CSF prostaglandin F2α in progressive MS. Issue 4 (August 2016) - Lam, Magda A.; Maghzal, Ghassan J.; Khademi, Mohsen; Piehl, Fredik; Ratzer, Rikke; Romme Christensen, Jeppe; Sellebjerg, Finn Thorup; Olsson, Tomas; Stocker, Roland
Abstract : Objective: We aimed to investigate the role of oxidative stress in the progression of multiple sclerosis (MS). Methods: We determined by liquid chromatography–tandem mass spectrometry nonenzymatic (F2 -isoprostanes) and enzymatic oxidation products of arachidonic acid (prostaglandin F2α [PGF2α ]) in plasma and CSF of 45 controls (other neurologic disease [OND] with no signs of inflammation) and 62 patients with MS. Oxidation products were correlated with disease severity and validated biomarkers of inflammation (chemokine ligand 13; matrix metalloproteinase-9; osteopontin) and axonal damage (neurofilament light protein). Results: Compared with OND controls, plasma concentrations of F2 -isoprostanes and PGF2α were significantly lower in patients with progressive disease, and decreased with increasing disability score (Expanded Disability Status Scale). In contrast, CSF concentrations of PGF2α, but not F2 -isoprostanes, were significantly higher in patients with progressive disease than OND controls ( p < 0.01). The content of PGF2α in CSF increased with disease severity ( p = 0.044) and patient age ( p = 0.022), although this increase could not be explained by age. CSF PGF2α decreased with natalizumab and methylprednisolone treatment and was unaffected by the use of nonsteroidal anti-inflammatory drug in secondary progressive MS. CSF PGF2α did not associate with validated CSF markers of inflammation and axonal damage that themselves did not associate with the Expanded Disability Status Scale. Conclusions: Our data suggest that MS progression is associated with low systemic oxidative activity. This may contribute to immune dysregulation with CNS inflammation accompanied by increased local cyclooxygenase-dependent lipid oxidation.